Perancangan Sistem Inventory Berbasis Web untuk Optimalisasi Manajemen Persediaan Barang di PT Bumi Daya Plaza - Ridho Esa Anugrah; Yudhistira Abdi Saputra; Wasis Haryono (Asosiasi Profesi Telekomunikasi Dan Informatika Indonesia, 2024)
PT Bumi Daya Plaza faces various obstacles in managing inventory because it still relies on a manual system based on Microsoft Excel. This approach causes a number of problems, such as recording errors, low data security, and limited real-time access, which negatively affect operational efficiency and customer satisfaction. This study aims to develop a web-based inventory system to overcome these problems. This system is designed to be able to monitor stock in real time, automate the reordering process, and generate accurate reports automatically. The research methodology includes interviews, observations, and document analysis to ensure user needs are met. The implementation results show that this system can improve work efficiency, reduce recording errors, and strengthen data-based decision making. With this innovation, PT Bumi Daya Plaza is expected to increase competitiveness and respond to market needs more effectively.